INCREASING THE STUDENTS’ ANTHUSIASM IN SPEAKING ENGLISH BY USING A PICTURE - Zuhriyah, S.S., M.Pd, Aminatuz (HERITAGE, 2015)
The problems of this research were how to increasing the students’ enthusiasm in speaking english by using a picture and how to motivate the students to apply it in their English. The research was guided by a conceptual framework leading to the using pictures through peer work to increasing the students’ enthusiasm in speaking English by using a picture during the process of classroom communication interaction. The research type was an action research. The subject consisted of 15 students of the first semester communication students of Univ. Yudharta in 2016-2017 academic years. The research data were collected using test (test after first treatment and test after the second treatment), observation for collecting data on the students’ motivation in to increasing the students’ enthusiasm in speaking English by using series pictures. The Data on vocabulary ability using picture were analyzed using the descriptive and statistic analysis, to know the improvement in mean students after the first cycle and the second cycle. Based on the first cycle, the students’ average was 60.5, then, on the second treatment, the students’ average increase to be 77,9. It can conclude that teaching English by using pictures can increase the students’ enthusiasm in speaking English.